2015
DOI: 10.1101/gad.242842.114
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionarily conserved DNA architecture determines target specificity of the TWIST family bHLH transcription factors

Abstract: Basic helix-loop-helix (bHLH) transcription factors recognize the canonical E-box (CANNTG) to regulate gene transcription; however, given the prevalence of E-boxes in a genome, it has been puzzling how individual bHLH proteins selectively recognize E-box sequences on their targets. TWIST is a bHLH transcription factor that promotes epithelial-mesenchymal transition (EMT) during development and tumor metastasis. High-resolution mapping of TWIST occupancy in human and Drosophila genomes reveals that TWIST, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 36 publications
6
72
0
Order By: Relevance
“…While appearing paradoxical, this is necessary to maintain a pool of osteo-PCs that can support balanced rates of osteoblast differentiation. Interestingly, Twist1/E-protein heterodimers have high affinity for tandem e-box elements in the Bmp4 promoter (Chang et al, 2015), and we find that high levels of Twist1 coincide with low and/or undetectable levels of Bmp2/4 expression in osteo-PCs. This suggests that Twist1 maintains an osteoprogenitor state, in part, through the repression of BMP signaling.…”
Section: Discussionmentioning
confidence: 72%
“…While appearing paradoxical, this is necessary to maintain a pool of osteo-PCs that can support balanced rates of osteoblast differentiation. Interestingly, Twist1/E-protein heterodimers have high affinity for tandem e-box elements in the Bmp4 promoter (Chang et al, 2015), and we find that high levels of Twist1 coincide with low and/or undetectable levels of Bmp2/4 expression in osteo-PCs. This suggests that Twist1 maintains an osteoprogenitor state, in part, through the repression of BMP signaling.…”
Section: Discussionmentioning
confidence: 72%
“…4d). These findings suggest that GFP-WR is interacting with TWIST1 via WR-WR binding, an interaction illustrated by recent studies of higher order TWIST1 complexes [17]. In order to determine whether GFP-WR-mediated inhibition of TWIST1-RELA binding impacted downstream signaling, we again employed a dual luciferase assay to quantify IL-8 promoter activity.…”
Section: Resultsmentioning
confidence: 84%
“…This domain is found in over one-third of Arabidopsis bHLH TF family members (Supplemental Data Set 3). The bHLH transcription factors usually function in dimer or tetramer form or by forming a complex with other TF family members (Ellenberger et al, 1994;Ma et al, 1994;Huffman et al, 2001;Li, 2014;Chang et al, 2015); often the bHLH motif is required for dimerization. In this study, we demonstrated that the plantspecific BIF domain is also important for the dimerization and the normal function of DYT1.…”
Section: The Bif Domain Is Required For Dyt1 Functionmentioning
confidence: 99%